2005
DOI: 10.1603/0022-0493-98.4.1374
|View full text |Cite
|
Sign up to set email alerts
|

Maize and Oat Antixenosis and Antibiosis Against <I>Delphacodes kuscheli</I> (Homoptera: Delphacidae), Vector of “Mal de Rio Cuarto” of Maize in Argentina

Abstract: "Mal de Rio Cuarto" (MRC) is the most important virus disease of maize, Zea mays L., in Argentina. Several maize lines show different levels of resistance to MRC in the field; however, no studies have been conducted to investigate resistance mechanisms against its insect vector, Delphacodes kuscheli Fennah (Homoptera: Delphacidae). Oat, Avena spp., is the main overwintering host of D. kuscheli and main source of populations that infest maize. Although oat varieties resistant to the greenbug, Schizaphis graminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…It was shown that this model is a particular case of a generalized von Bertalanffy model (Day 1966). Only for peak oviposited females, apart from its weight we added the weight represented by the number of mature oocytes calculated as: WE (t=38) = 20 • W (t=4) , where 20 represents the mean maximum number of eggs deposited during peak reproduction (Costamagna et al 2005) and W (t=4) the weight of an individual young egg.…”
Section: The Weight Of An Individual Host As An Indicator Of the Amoumentioning
confidence: 99%
“…It was shown that this model is a particular case of a generalized von Bertalanffy model (Day 1966). Only for peak oviposited females, apart from its weight we added the weight represented by the number of mature oocytes calculated as: WE (t=38) = 20 • W (t=4) , where 20 represents the mean maximum number of eggs deposited during peak reproduction (Costamagna et al 2005) and W (t=4) the weight of an individual young egg.…”
Section: The Weight Of An Individual Host As An Indicator Of the Amoumentioning
confidence: 99%
“…Nevertheless, their resistance to infestation by D. kuscheli has scarcely been studied. Antixenotic and antibiotic resistance to D. kuscheli of oat cultivars, carrying resistance to greenbug, Schizaphis graminum (Rondani), has been reported previously (Costamagna et al 2005).…”
mentioning
confidence: 80%
“…The telomeric region of the 6A chromosome probably carries genes that enable the plant to tolerate biotic stresses. Nonetheless, the Þrst report of resistance against D. kuscheli in oats indicates an absence of antixenosis and antibiosis in commercial greenbugresistant oat cultivars (Costamagna et al 2005). Stress signaling pathways are not independent, ABA, ethylene, jasmonic acid, and salicylic acid are produced by plants under stress, and when exogenously applied, they switch on a number of genes that respond to environmental or biotic stress (Yamaguchi-Shinosaki and Shinosaki 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Maize antixenosis has been demonstrated in the westem corn rootworm (Bemklau et al 2010), planthoppers (Costamagna et al 2005), and European com borer (Robinson et al 1978). In some instances, trade offs in maize antixenosis have been identified, whereby the activation of a defense mechanism against one herbivore or pathogen makes the plant more attractive than another (Ballhom2011).…”
Section: Plant Resistance Mechanismsmentioning
confidence: 99%